دور التكوين في تحسين أداء العاملين دراسة ميدانية بالمؤسسة العمومية للصحة الجوارية جامعة - عبد الحميد قمودة; حليمة حميدي (جامعة الوادي - University of Eloued, 2025)
"تهدف هذه الدراسة إلى معرفة دور التكوين في تحسين أداء العاملين ، من خلال دراسة ميدانية تمت في المؤسسة العمومية للصحة الجوارية جامعة ، تم جمع البيانات من خلال استبانة تحتوي على مجموعة من العبارات المتعلقة بالتكوين تم توزيعها على فئة الموظفين الإداريين والتي قدرت بـــ: 46 مفردة ، وقد تم تحليل البيانات الواردة للاستبيانات عن طريق الحزم الإحصائية للعلوم الاجتماعية (spss),بالاعتماد على المتوسطات الحسابية , والإنحرافات المعيارية , ومعاملات الإرتباط , والوزن النسبي. وقد خلصت الدراسة على مجموعة من النتائج أهمها: - للتكوين دور كبير في تحسين أداء العاملين بالمؤسسة العمومية للصحة الجوارية جامعة. - يساهم التكوين وبشكل كبير في تحسين أداء العاملين بالمؤسسة العمومية للصحة الجوارية جامعة ، حيث أظهرت النتائج قبولًا عامًا لأهميته وتأثيره الإيجابي على اكتساب مهارات جديدة والتي تأدي بدورها إلى زيادة الكفاءة. - اكتساب المهارات والمعارف الجديدة بعد التكوين له دورًا فعال في زيادة فاعلية أداء العاملين وتعزيز رغبتهم في تحقيق الأهداف المؤسسية. "This study aims to indentify the role of training improving the employee performance through a field study conducted at the public instution for neighborhood health. University . data were collected through a questionnaire containing a set of statements related to training . which were distributed to the category of administrative employees. estimated at:46 items. The data received from questionnaires where analyzed using the statistice package for the social scciences (spss). Relying on arithmetc means. Standard deviatinos .correlation coefficients .and relative weight the study concluded . with a set results . the most important of which are: -Triningplays major role in improving the performance of employees at the public Institution for Neighborhood health. University. -Training contributes significantly to improving the performance of emplyees at the public Institution for Neigh borhood health .University. The reslts showed general acceptance .of its importance and positive impact on acquiring new skills. which in turrn leads to increased efficiency. Acquiring new skills and knowledge after training plays and effective role in increasing the effectiveness of employee performance and enhancing their desire to achieve organizational goals.
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل
Keywords: المهارات; أداء العاملين; الأداء; التكويـــــن; Training; Performance; employee performance; Skills